2021
DOI: 10.3832/ifor3489-014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of thinning and mixing on stand spatial structure: a case study of Chinese fir plantations

et al.

Abstract: The regular planting and periodic harvesting of a single tree species are features of plantations, which are associated with a reduction of biodiversity. Such plantations are strongly encouraged to be converted into mixed forests. However, the spatial structure dynamics of plantations during the conversion process are poorly understood. In subtropical regions, thinned forest of Chinese fir (Cunninghamia lanceolata [Lamb.] Hook.) and mixed forest of Chinese fir and Michelia macclurei Dandy are considered two id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Baran et al (2020) found that trees tend to be aggregated in unmanaged forests while they showed random patterns in managed forests. However, independent patterns were found to be intensely dominant in interspecific interactions in many subtropical and tropical natural forests (Nguyen et al 2018a;Li et al 2020b) supporting the unified neutral theory (Hubbell 2006).…”
Section: Unmarked Analysismentioning
confidence: 61%
See 4 more Smart Citations
“…Baran et al (2020) found that trees tend to be aggregated in unmanaged forests while they showed random patterns in managed forests. However, independent patterns were found to be intensely dominant in interspecific interactions in many subtropical and tropical natural forests (Nguyen et al 2018a;Li et al 2020b) supporting the unified neutral theory (Hubbell 2006).…”
Section: Unmarked Analysismentioning
confidence: 61%
“…Suzuki et al (2005) used the expression "complete spatial randomness" as a synonym of "complete spatial independence" in the univariate analysis. Li et al (2020b) used also similar terms (i.e. aggregation, regularity, and randomness) in either uni-or bivariate analysis.…”
Section: Description Of Sppa Results and Their Interpretationmentioning
confidence: 99%
See 3 more Smart Citations